Jane Eyre and Wide Sargasso Sea’s Treatment of Feminism and its Reflection in Character Analysis - Rakhimova Ugiloy Akbarovna, (Universitas Muhammadiyah Sidoarjo, 2022)
“Jane Eyre” and “Wide Sargasso Sea” are regarded as the masterpieces that vividly express theelements of feminism. Before analyzing and proving this idea,it is necessary to determine and definethe concept of feminism.One of the best works was Charlotte Bronte’s “Jane Eyre”. At that time, forJane, as a member of the lowest class, she is always looked down upon by those potentates withmoney and power. For people like her, they have no dignity; the rich can treat them at random andneed not bother to give them any esteem. But Jane Eyre never surrenders to those snobbish peoplewho despise the poor and the weak parochially and ruthlessly. In her whole life, she plunges herselfinto struggling for esteem which in her mind is deserved by any human being rather than a privilegefor the wealthy people.